O-006 Expansion of Immunologically-Relevant E. Coli in the Intestinal Microbiota of Patients with IBD-Associated Spondyloarthritis Promotes Mucosal RORgt-Dependent Immunity. (March 2016) - Kivolowitz, Charles; Abdulhamid, Ahmed; Victorio, Daniel; Castellanos, Jim; Simpson, Kenneth; Scherl, Ellen; Longman, Randy
Abstract : Background: Spondyloarthritis (SpA) is the most common extra-intestinal manifestation in patients with inflammatory bowel disease (IBD), but the underlying pathogenesis that links IBD and SpA is unknown. Since IBD involves a dysregulated intestinal immune response to luminal microbial antigens and the abundance of particular microbial clades has been correlated to other arthropathies, we hypothesized that IBD-associated SpA (IBD-SpA) has a characteristic immunogenic microbial signature. Methods: To test this hypothesis, we evaluated the fecal microbiome of 59 IBD patients (40 Crohn's disease [CD], 19 ulcerative colitis [UC]) using 16S rRNA sequence analysis. The Bath Ankylosing Spondyloarthritis Disease Activity Index (BASDAI) and 44-point joint count was used to clinically characterize inflammatory joint disease activity. To profile the immunologically relevant fecal microbiota, we sorted and sequenced IgA- and IgG-coated microbes from CD and CD-SpA patients. To test the functional significance of patient-derived E. coli, we cultured isolates from IBD-SpA patients by limiting dilution anaerobic culture and assessed their effect on intestinal immune cell activity in gnotobiotic mice. Results: Of the patients evaluated, 34 patients had SpA based on the Assessment of Spondyloarthritis international Society (ASAS) guidelines (25 CD-SpA, 9 UC-SpA). BASDAI and 44-point joint count significantly differentiated IBD-SpA versus IBD controls (4.4 versus 2.4, P = 0.003; 3.1 versus 0.9, P = 0.03, respectively). Compositional analysis of the fecal microbiome revealed a significant expansion of Enterobacteriaceae in CD-SpA compared to CD alone. Significant enrichment in the OTU E. coli /Shigella was seen in IgA- and IgG-coated fractions of patients with CD-SpA. Colonization of germ-free C57BL/6 mice with IBD-SpA patient-derived E. coli robustly induced lamina propria T helper cells expressing RORgt+ (Th17) cells and Foxp3+/RORgt in vivo . Conclusions: Our findings reveal that the intestinal microbiota of patients with IBD-SpA is selectively enriched in immunologically relevant E. coli and promote RORgt-dependent intestinal immunity. Follow up mechanistic studies will help to define potential diagnostic and therapeutic targets in the relationship between intestinal microbiota and IBD-associated SpA.